Blood eosinophil reference values and determinants in a representative adult population - Reshed Abohalaka, MSc; Selin Ercan, MD; Lauri Lehtimäki, MD, PhD; Saliha Selin Özuygur Ermis, MD; Daniil Lisik, MD; Muwada Bashir Awad Bashir, MD, PhD; Radhika Jadhav, MD; Linda Ekerljung, MD, PhD; Göran Wennergren, MD, PhD; Jan Lötvall, MD, PhD; Teet Pullerits, MD, PhD; Helena Backman, PhD; et al. (Journal of Allergy and Clinical Immunology: Global)
Background: The use of blood eosinophil count (BEC) as a prognostic biomarker in the management of conditions such as asthma and chronic obstructive pulmonary disease (COPD) may be complicated by factors such as atopy, age, sex, smoking, and comorbidities. Objective: We sought to produce reference values for BEC, considering age, asthma, COPD, and clinical allergy for the general adult population. Methods: The West Sweden Asthma Study constitutes a population-representative clinical epidemiological cohort of randomly selected adults in Western Sweden. From this cohort, 1145 individuals took part in clinical examinations, including skin prick testing, specific IgE, and BEC. Results: The upper limit (95th percentile) of BEC varied by age. It ranged from 400 to 500 cells/μL in the full sample and from 300 to 400 cells/μL in subjects without asthma, COPD, and clinical allergy (n = 710). Sex, smoking, atopy, clinical allergy, obesity, asthma, COPD, diabetes, and hypertension were statistically significantly associated with higher BEC levels. However, only asthma and clinical allergy in the full sample, and obesity and diabetes in those without asthma, COPD, or clinical allergy, remained statistically significant with higher BEC levels in multivariable regression analyses. Conclusions: In a population-representative sample, the upper limit of BEC in healthy adults ranged between 300 and 400 cells/μL, varying by age. Age, smoking, obesity, asthma, COPD, and clinical allergy influence BEC levels and should be considered in clinical interpretation.